Ascorbyl‐6‐O‐oleate: A Bioconjugate Antioxidant Lipid. Issue 6 (12th February 2020) - Perini, Ilaria; Ambrosi, Moira; Tanini, Damiano; Ninham, Barry W.; Capperucci, Antonella; Nostro, Pierandrea Lo
Abstract: Ascorbyl‐6‐O‐oleate (Asc‐OL) was synthesized enzimatically and studied in the pure state and in aqueous dispersions. Small‐angle X‐ray scattering (SAXS), differential scanning calorimetry (DSC), Fourier transformed infrared (FTIR) spectroscopy experiments and antioxidant tests were conducted in order to characterize the compound and to evaluate its reducing properties. Asc‐OL is a bioconjugate molecule, in fact it combines the main physico‐chemical features of the two parent molecules, i. e. the redox and acidic properties of Vitamin C and the fluid‐like state of oleic acid. The appropriate tests were carried out to confirm the excellent radical scavenging activities of Asc‐OL, that turned out to be a promising candidate for the stabilization, transport and protection against radical attack of valuable hydrophobic active ingredients used in food and pharmaceutical formulations. Abstract : Ascorbyl‐oleate (Asc‐OL) is an antioxidant bioconjugate with an amphiphilic nature imparted by the presence of the hydrophilic Vitamin C head and the lipophilic, liquid‐like oleic acid chain. New experiments elucidate the shape, size and thermal properties of the micellar aggregates produced in water. DPPH and linoleate tests suggest that Asc‐OL is a green excellent candidate for the stabilization and vehiculation of valuable molecules.